MAK ANDAM DAN PAK LEBAY DALAM PERGESERAN MAKNA PROSES PERKAWINAN MELAYU DI SUNGAI PAKNING KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - ", Fatimah; Rosaliza, Mita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Sungai Pakning Bukit Batu Sub-district Bengkalis Regency. The purpose of this research is to know the Implementation of Berandam in Malay Customary Process in Pakning River, Bukit Batu Sub-district, Bengkalis Regency. The focus of this research is to analyze the change of meaning on the ritual of berandam in Pakning River, Bukit Batu District, Bengkalis Regency. The technique of determining the sample by purposive sampling. and set the number of samples as many as 3 people. The author uses qualitative descriptive method and Instrument data is observation and depth interview. The research conducted to find the meaning of berandam in process of marriage of adat malay is as follows: Cleansing Lahiriah, research conducted to find that the procession berandam aims to clean the body of the bride so that the glow when seen the wedding guests, if awake circumstances bride candidate then awake also inward . Cleansing the Heart, Research has found that a series of rituals performed at the time of berandam is intended to open the joy and happiness of the bride. The Symbol of Preparedness for Women to Take the Life of the Household, Research has found that performing a ritul berandam is similar to preparing a virgin to be a great woman in the household to be developed later. For that virgin to be married to be purified first through a ritual berandam. Changes in people's perceptions of the ritual of berandam are as follows: Contrary to Religious Values, Research conducted found the fact that people try to leave this ritual berandam because it is against the religion of Islam. Tradition of this berandam done indeed by shaving fine hair in some parts of the female body of the bride. And indeed in Islam itself shaved smooth hair is not allowed, Not in accordance with the Marriage Event of the Modern Age, Research conducted found that people are less interested in performing the tradition of berandam is because the ritual is not suitable for dipadupadan kan with modern wedding events that tend to be modern. Keywords: Social Change, Culture